DESIGN AND IMPLEMENTATION OF A BALANCED THREE-PHASE POWER PROTECTION SYSTEM (FULafia Journal of Science and Technology, 2019)
This work considers the design and implementation of a balanced three-phase power protection system used to load sharing formula at consumer receiving end to ensure uniform distribution of the available threephase voltage supply-source. Various methods have been developed with the main objective to provide an engineering solution to the effects causing unbalanced three-phase voltage supply. The engineering solution considered in this research work was designed and implemented with the use of local raw materials in Nigeria. This solution is thus achieved by employing voltage-tap changing technique at both primary and secondary sides of the three-phase transformer. The transformer is auto-winding star connected type where its star point is taken as system design-neutral point. However, whether the unbalanced voltage is due to an unbalanced single phase loading or unstable network supply within the plant, this system can continuously correct and adjust the correction level as required to ±0.4% of the set nominal voltage, and zero the voltage imbalances to give out 100% balanced voltage.